Stereoselective synthesis of a 9-O-sulfo Neu5Gc-capped O-linked oligosaccharide found on the sea urchin egg receptor. Issue 1 (19th November 2018) - Das, Anindya; Li, Pei-Jhen; Adak, Avijit K.; Wu, Hsin-Ru; Anwar, Mohammad Tarique; Chiang, Pei-Yun; Sun, Chung-Ming; Hwu, Jih-Ru; Lin, Chun-Cheng
Abstract : The first total synthesis of a serine bearing α2→5-Oglycolyl -linked oligoNeu5Gc found on sea urchin egg cell surfaces has been accomplished. Abstract : A straightforward synthesis of the α(2→5)-linked 9- O -sulfated Neu5Gc-capped O-linked tetrasaccharide (1 ) identified in the egg cell surface glycoproteins of the sea urchin Strongylocentrotus purpuratu s receptor for sperm is reported. The construction of the α(2→5)Neu5Gc trimer by the formation of an amide linkage rather than a glycosidic bond avoids the requirement for α-stereoselective glycosylation. To highlight this amide bond formation strategy as a relatively facile method for synthesizing oligo-Neu5Gc containing O-linked glycans, its versatility is demonstrated by application to the coupling of SO3 H-9Neu5Gcα(2→5)Neu5Gc glycolic acid and a sialyl-Tn-derived amine for achieving the target tetrasaccharide. This synthetic strategy may be implemented in the generation of other structurally similar O -sulfo Neu5Gc-capped α2→5-Oglycolyl -linked oligo-Neu5Gc chains, enabling additional biological and chemical investigations.